2020
DOI: 10.1186/s12967-020-02366-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hypoxia-immune-based microenvironment gene signature for risk stratification in gastric cancer

Abstract: Background: Increasing evidences have found that the clinical importance of the interaction between hypoxia and immune status in gastric cancer microenvironment. However, reliable prognostic signatures based on combination of hypoxia and immune status have not been well-established. This study aimed to develop a hypoxia-immune-based gene signature for risk stratification in gastric cancer. Methods: Hypoxia and immune status was estimated with transcriptomic profiles for a discovery cohort from GEO database usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 43 publications
0
70
0
Order By: Relevance
“…The immune-related signature has been proposed in several cancers, including glioblastoma, pancreatic cancer, and renal carcinoma, which performed well in clinical validation [14][15][16]. However, these studies have several limitations, such as relatively small sample sizes and lack of independent validation.…”
Section: Discussionmentioning
confidence: 99%
“…The immune-related signature has been proposed in several cancers, including glioblastoma, pancreatic cancer, and renal carcinoma, which performed well in clinical validation [14][15][16]. However, these studies have several limitations, such as relatively small sample sizes and lack of independent validation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a variety of signatures based on these genes have demonstrated an excellent ability in predicting prognosis for GC, and been validated in multiple independent datasets. [13][14][15] Owing to the importance of glycolysis pathway in regulating tumorigenesis, this work is aim to develop a list of glycolysis-related genes for risk stratification in GC patients. In this study, 9 glycolysis-related genes were identified to construct a novel scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing specific gene expression, the algorithm infers the infiltration of stromal and immune cells and assesses tumor purity (18). Previous reports have applied the ESTIMATE to build prognostic models associated with TME in various malignancies, indicating the feasibility of the algorithm in the prediction of survival outcome (19)(20)(21). In the present study, we aimed to develop a Prognostic Microenvironment-related Immune Signature via ESTIMATE (PROMISE model) for glioma using expression profiles in The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) database.…”
Section: Introductionmentioning
confidence: 99%